(untitled) (LEARNing Landscapes, 2013)
This article gives some background information on the authors’ forthcoming book, The State of Learning. There are many challenges facing educators who want to bring education into the 21st century. At the same time, the explosion of technology has the potential to make education more available and influential than ever before. Education is taking place on a large stage and is not just confined to schools. We must rethink the foundations of education so it can truly benefit from new technology.